Growth expectations, undue optimism, and short-run fluctuations: conference paper - Enders, Zeno; Kleemann, Michael; Müller, Gernot J. (Jahrestagung des Vereins für Socialpolitik 2013, 2013)
Expectations matter for economic activity. To the extent that they are fundamentally unwarranted, they represent "undue optimism or pessimism" (Pigou, 1927). In this paper, we identify empirically the effect of undue optimism/pessism ("optimism shocks") on economic activity. In a first step, we compute an expectation error regarding current economic activity: the difference of the Ifo index of economic activity and its consensus forecast, compiled simultaneously and independently. The resulting "Ifo innovations" may represent either fundamental innovations or optimism shocks. In a second step, we impose long-run restrictions on a VAR model to disentangle the effects of both shocks. We find that optimism shocks - in line with theory - reduce Ifo innovations, but raise economic activity. They account for up to 30% of short-run fluctuations in industrial production.
Keywords: Graue Literatur; Konferenzschrift